Alternative problems in the development of the Thai state and society in the past 20 years - Noiwiang, Sayan (Thai Social Science Journal, 2025)
Thai society has undergone periodic social and economic development. Until now, we have reached an important point of choice in the development of the state and society in the midst of changes in various societies around the world. The past development guidelines for the state and Thai society have always had the government sector play a role in setting and leading policy, but in the past 20 years, political reform has resulted in the political party playing an important role in setting policies and leading the development of the state and society. Alternative problems in the development of the Thai state and society with concepts and directions that are different from the Thaksin government era, emphasize modernity from Dual policies to the government of General Prayut, who drives the country with the Thailand 4.0 policy, while at present Thai society is still unable to find a perfect balance in state development options. One option that should be chosen is to develop a middle path where every political institution must sacrifice for society